2008
DOI: 10.1098/rsbl.2007.0614
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns in the acoustic signals of beaked whales at Cross Seamount

Abstract: Seamounts may influence the distribution of marine mammals through a combination of increased ocean mixing, enhanced local productivity and greater prey availability. To study the effects of seamounts on the presence and acoustic behaviour of cetaceans, we deployed a high-frequency acoustic recording package on the summit of Cross Seamount during April through October 2005. The most frequently detected cetacean vocalizations were echolocation sounds similar to those produced by ziphiid and mesoplodont beaked w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 16 publications
2
39
1
Order By: Relevance
“…The resulting patterns in prediction maps produced for 2 different seasons (Fig. 11) are in good agreement with general patterns observed for the depth of the SSL in the North Pacific: from 200 m near the coast to 400 m farther offshore in the California Current, and ~500 to 600 m near Hawaii (Tont 1975, Kalish et al 1986, Johnston et al 2008.…”
Section: Modelingsupporting
confidence: 67%
“…The resulting patterns in prediction maps produced for 2 different seasons (Fig. 11) are in good agreement with general patterns observed for the depth of the SSL in the North Pacific: from 200 m near the coast to 400 m farther offshore in the California Current, and ~500 to 600 m near Hawaii (Tont 1975, Kalish et al 1986, Johnston et al 2008.…”
Section: Modelingsupporting
confidence: 67%
“…We believe this is one of the reasons for the much clear day-night differences in backscattering intensity in Gigante, as opposed to Condor where diel changes were small. Although video imagery and net sampling provided only limited evidence of the presence of vertically migrant fishes on the Condor plateau (Porteiro et al, 2011, topographic blockage has been suggested as one of the mechanisms responsible for the increased nighttime micronekton abundance at other shallow/intermediate seamounts (Boehlert, 1988;Johnston et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Like other topographic features, seamounts can shape the aggregation of pelagic organisms and many seamounts support unusually high biomass of micronekton SLs compared to the surrounding ocean (e.g., Boehlert, 1988;Johnston et al, 2008;Letessier et al, in press). Various non-exclusive mechanisms may explain increased micronekton biomass over seamounts.…”
mentioning
confidence: 99%
“…All three species produce upsweep frequency modulated ͑FM͒ pulses, which are species and activity specific. Johnston et al ͑2008͒ andMcDonald et al ͑2009͒ report an FM ultrasonic sound of unknown origin with beaked whale characteristics, discovered on a long-term broadband acoustic recording from Cross Seamount, HI. Other beaked whales within the genus Hyperoodon and Berardius also use short duration, broadband echolocation clicks but restrictions in sampling frequency do not allow for judgment whether these signals have a frequency sweep a͒ ͑Dawson et al, 1998;Rogers and Brown, 1999;Hooker and Whitehead, 2002͒.…”
Section: Introductionmentioning
confidence: 98%